Innovation, Investment and Intellectual Property in South Korea Park to Park - Taplin, Ruth (Routledge Studies in the Growth Economies of Asia Ser, 2018)
"South Korea known as the hermit kingdom was wrenched from its isolation in the mid-seventies with the forced industialisation of its economy by Park Chung-hee during his dictatorial regime. This led South Korea to becoming the most rapidly industialised country in the world with world class technology and a population who are largely digitally proficient. The course is charted from the rule of Park Chung-hee to his democratically elected daughter President Park Geun-hye who is now on trial for corruption. The legacy of the Park to Park era is not only the most fruitful in Korean history but the most tumultuous, most recently because of the accelerated nuclear ambitions of North Korea. The analysis is through the framework of investment, innovation and intellectual property rights and the double edged sword of cult and rapid action, so central to Korean culture."--